2022
DOI: 10.1371/journal.pone.0263811
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinant factors of intimate partner violence among reproductive age group women in Ethiopia: Using generalized structural equation modeling

Abstract: Introduction Intimate Partner Violence (IPV) is the most serious and pervasive yet under-recognized human rights violation in the world, particularly in Ethiopia. Hence, the objective of this study was to find the spatial distribution of IPV and its determinant factors in Ethiopia. Methods Secondary data analysis was conducted among 2,687 reproductive age group women (15–49 years). The distribution of IPV across the country was observed by ArcGIS software. In SaTScan software, the Bernoulli model was fitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The lower likelihood of the simultaneous occurrence of IPV and underweight among these women could be due to the complexity of the interplay of different factors acting together to either protect or expose women to IPV and undernutrition. For women living in urban areas, greater autonomy [30] and the lesser influence of cultural norms and expectations around gender roles in the urban environment provides an escape from vices such as IPV. This notwithstanding,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower likelihood of the simultaneous occurrence of IPV and underweight among these women could be due to the complexity of the interplay of different factors acting together to either protect or expose women to IPV and undernutrition. For women living in urban areas, greater autonomy [30] and the lesser influence of cultural norms and expectations around gender roles in the urban environment provides an escape from vices such as IPV. This notwithstanding,…”
Section: Discussionmentioning
confidence: 99%
“…This The results of the spatial models show strong spatial clustering in IPV and undernutrition within and across the West African region. Some studies have shown spatial clustering in IPV in sub-Saharan Africa [35,36] Nigeria [37][38][39][40][41], Ghana [42], Ethiopia [30,43] and South Africa [44] but very few studies have explored the simultaneous occurrence of IPV and PLOS GLOBAL PUBLIC HEALTH undernutrition in similar geographic spaces. The positive linear relationship between IPV and underweight among women in some regions of Mali; all parts of Sierra Leone and Liberia and neighboring Cote d'Ivoire, Ghana, and Togo as was found in the present study could be because of common contextual/place-based socio-cultural beliefs and practices that perpetuate male dominance and limits women autonomy thus exposing women in these regions to the risk of IPV and undernutrition.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…For each item, a woman has participated in household decision-making when she was involved (alone or jointly with a partner or someone else) in all decisions regarding her own healthcare, large household purchases and visits to her family or relatives. 2 Responses were recoded as ‘yes’ or ‘no’.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Worldwide, around 30% of women aged 15–49 years have experienced physical and/or sexual violence by their intimate partner at least once in their lifetime. 2 7 IPV varies significantly across regions. A lower prevalence of IPV was observed in the Western Pacific (20%), while the prevalence was much higher in the WHO African and South-East Asia regions (33%), 7 due to the high social acceptance of violence and socioeconomic vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation